2001
DOI: 10.1002/etc.5620200114
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of estrogenic hormones in municipal wastewater effluent and surface water using enzyme‐linked immunosorbent assay and gas chromatography/tandem mass spectrometry

Abstract: Although the estrogenic hormones 17 beta-estradiol and 17 alpha-ethinyl estradiol can be quantified in polluted waters by gas chromatography/mass spectrometry (GC/MS) and gas chromatography/tandem mass spectrometry (GC/MS/MS), the compounds often are present at concentrations below detection limits. Enzyme-linked immunosorbent assays (ELISAs) provide a sensitive and robust means of quantifying estrogenic hormones in wastewater effluents and surface waters. Results from ELISA analysis of estrogenic hormones in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
159
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 347 publications
(171 citation statements)
references
References 19 publications
8
159
1
3
Order By: Relevance
“…17- β Estradiol levels of female control rats, oophorectomized female rats, and oophorectomized female rats treated with exogenous estrogen replacement therapy were measured using an Estradiol ELISA Kit (Neogen Corporation, Lexington, KY) unpublished data, [24, 25], vaginal swabs (uterus) were performed to document loss of epithelium and to document a relative “post-menopausal” state. Briefly, samples or standards were added to the microplate, followed by the diluted enzyme conjugate.…”
Section: Methodsmentioning
confidence: 99%
“…17- β Estradiol levels of female control rats, oophorectomized female rats, and oophorectomized female rats treated with exogenous estrogen replacement therapy were measured using an Estradiol ELISA Kit (Neogen Corporation, Lexington, KY) unpublished data, [24, 25], vaginal swabs (uterus) were performed to document loss of epithelium and to document a relative “post-menopausal” state. Briefly, samples or standards were added to the microplate, followed by the diluted enzyme conjugate.…”
Section: Methodsmentioning
confidence: 99%
“…The incomplete removal by publicly owned treatment works (POTWs) of excreted endogenous estrogens and prescribed estrogens leads to their introduction into surface waters and potentially into drinking water sources that rely on surface water. Estrogens, specifically estrone (E1), 17β-estradiol (E2), estriol (E3), and ethinyl estradiol (EE2), have been detected in numerous studies of wastewater influents and effluents (Baronti et al 2000; Belfroid et al 1999; Desbrow et al 1998; Ferguson et al 2001; Heberer 2002; Huang and Sedlak 2001; Huggett et al 2003; Laganà et al 2000; Mouatassim-Souali et al 2003; Nasu et al 2001; Rodgers-Gray et al 2000; Spengler et al 2001; Ternes et al 1999a, 1999b, 2002), and their presence has been confirmed in U.S. and European surface waters (Aherne and Briggs 1989; Belfroid et al 1999; Heberer 2002; Kolodziej et al 2003; Kolpin et al 2002; Kuch and Ballschmiter 2001). More recently, several estrogens have also been detected in the source water of drinking water treatment plants but not in the finished water (Benotti et al 2009).…”
mentioning
confidence: 99%
“…At low extent of pollution the method could be used in conjunction with ELISA technique. Huang & Sedlak (2001) Figure 4. Chromatogram of E2 and EE2 at 100 ng/ml and 250 ng/ml…”
Section: Methods Sensitivitymentioning
confidence: 99%